Allelopathic effects of actinobacterial isolates on seed germination and early seedling growth of velvetleaf (Abutilon theophrasti Medik.) - Šantrić, Ljiljana R; Radivojević, Ljiljana; Gajić Umiljendić, Jelena; Sarić-Krsmanović, Marija (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2022)
This study aimed to examine in vitro allelopathic effects of actinobacterial isolates on seed germination and early seedling growth of velvetleaf (Abutilon theophrasti). Thirtyfive actinobacterial isolates were obtained from soil and compost in different phases of composting. Also, an experiment variant involving the herbicide mesotrione was set in the recommended amount of application, as a reference standard. The experimental results indicate statistically significant differences (p
Keywords: actinobacteria; velvetleaf; seed germination; allelopathy